Possibilities of energy information monitoring and screening test of ecological additional burden - A. J. Chijov; E. B. Hlebtsova; M. J. Puchkov (Юг России: экология, развитие, 2015)
It is described that geopathogenic zones render the disadvantage influence on normal operating the organism of the person, break natural for it biorhythms. Under long influence geopathogenic zones appear the different diseases. Scientific studies of the last years have shown that to such diseases possible to refer: vegetative nervous system, psychoemotional of the deflection, exhaustion of immune system, development tumour processes, breaches on the part of gastrointestinal tract, bronchopulmonary of the system, endocrine system, diseases joint.